2011
DOI: 10.1007/s11064-010-0397-7
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to Myelin P0 and Ceramide Perpetuate Neuropathy in Long Standing Treated Leprosy Patients

Abstract: Anti neural antibodies are known to play a role in the immunopathogenesis of nerve damage in leprosy and HIV/AIDS. Myelin Protein zero (P0) and ceramide are two nerve components which maintain the integrity of the peripheral nerve. The present study was undertaken to identify antibodies to myelin P0 and ceramide in the sera of treated leprosy patients, HIV positive individuals and healthy subjects using enzyme linked immunosorbant assay (ELISA). The results revealed that treated leprosy patients continue to ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…The maximum fold increase was observed in Ceramide antibody followed by TNF-α, followed by S100 antibody and PGL-1 (Table 1 and Figure 2) suggesting the combination of these four serological markers could be a choice to understand reaction and their relationship to nerve damage. In addition, to the above mentioned four serological markers other inflammatory and autoimmune markers which have a fold increase such as Interferon-inducible protein-10 (IP-10) [22] and Myelin P0 [23-25] should be explored for understanding the nerve damage.…”
Section: Discussionmentioning
confidence: 99%
“…The maximum fold increase was observed in Ceramide antibody followed by TNF-α, followed by S100 antibody and PGL-1 (Table 1 and Figure 2) suggesting the combination of these four serological markers could be a choice to understand reaction and their relationship to nerve damage. In addition, to the above mentioned four serological markers other inflammatory and autoimmune markers which have a fold increase such as Interferon-inducible protein-10 (IP-10) [22] and Myelin P0 [23-25] should be explored for understanding the nerve damage.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that in long-standing treated leprosy patients, the persistent bacterial antigen can incite nerve autoantibodies that can perpetuate neuropathy. [ 23 ] A study from Brazil observed that the impairment status worsened in 40% of patients 10 years after RFT. [ 24 ] Studies have also shown that the cumulative probability of worsening of the physical disability grade of persons treated and declared cured of leprosy increases with time.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that nerve function impairment (NFI) once acquired worsens with time, especially in MB patients[ 34 ] and neuritis/new deformities continue to develop in certain forms of leprosy even after RFT. [ 35 36 ]…”
Section: Discussionmentioning
confidence: 99%